2019
DOI: 10.1186/s13007-019-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput long paired-end sequencing of a Fosmid library by PacBio

Abstract: BackgroundLarge insert paired-end sequencing technologies are important tools for assembling genomes, delineating associated breakpoints and detecting structural rearrangements. To facilitate the comprehensive detection of inter- and intra-chromosomal structural rearrangements or variants (SVs) and complex genome assembly with long repeats and segmental duplications, we developed a new method based on single-molecule real-time synthesis sequencing technology for generating long paired-end sequences of large in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Our investigation showed the discrepancy of genes and proteins between the Cytoplasmic Male Sterile Line and its Maintainer Line in Welsh onion, thereby furnishing a molecular basis for plant breeding. The third‐generation sequencing technology generates long reads and is especially advantageous for non‐model species lacking whole‐genome sequencing data (Dai et al, 2019). In this research, the method was utilized to found the FL transcriptome of flowers, which was subsequently utilized as reference transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation showed the discrepancy of genes and proteins between the Cytoplasmic Male Sterile Line and its Maintainer Line in Welsh onion, thereby furnishing a molecular basis for plant breeding. The third‐generation sequencing technology generates long reads and is especially advantageous for non‐model species lacking whole‐genome sequencing data (Dai et al, 2019). In this research, the method was utilized to found the FL transcriptome of flowers, which was subsequently utilized as reference transcript.…”
Section: Discussionmentioning
confidence: 99%
“…BAC-anchor determines general paired BESs by using specific restriction enzyme sites and searching for utlra-long paired-end subreads containing large internal gaps. We previously also developed a high-throughput approach for long accurate BES profiling with PacBio sequencing technology [ 30 ]. However, these approaches focused on paired BES profiles, and they are hard to trace BESs of specific clones in 384-plate wells.…”
Section: Discussionmentioning
confidence: 99%
“…Gene sequencing, including first-, second- and third-generation sequencing (TGS), is the most accurate method of identifying infectious pathogens; it has been successfully used for the diagnosis of known pathogens and the identification of unknown pathogens. First generation sequencing, represented by Sanger sequencing, is mainly used for targeted sequencing to reveal the sequences of several specific low-throughput sites, which is only suitable for small-scale analysis ( 93 ). With the completion of the Human Genome Project in the early 21st century and the rapid development of sequencing technology, high-throughput and low-cost next-generation sequencing (NGS) and TGS technologies have emerged ( 94 , 95 ).…”
Section: High-throughput Sequencingmentioning
confidence: 99%